Assessing environmental impact of genetically modified seeds in Brazilian agriculture - Seixas, Renato Nunes de Lima; Silveira, José Maria Ferreira Jardim da; Ferrari, Vinícius Eduardo (Frontiers in Bioengineering and Biotechnology, 2022)
Genetically modified (GM) seeds have had relevant impacts on worldwide agriculture, even with a limited number of essential traits launched in the markets. The focus on platform crops has favored the combination of traditional breeding, GM insertion, and diffusion in agriculture. The results are not limited to the direct impact on growers' performance but in the intensive and extensive margin of the global agricultural market, generating an uneven distribution of crops worldwide and raising concerns about food safety. One of the remarkable features of the GM traits has been the close link with pest and weed control systems. We investigate the environmental effects due to pesticides on two different genetically modified (GM) seeds: insect-resistant (IR) cotton and herbicide-tolerant (HT) soybeans, in a particular period of Brazilian agriculture, 2009-2013. We use a dataset on commercial farms' use of pesticides and biotechnology in Brazil to document the environmental effects of GM traits. We explore within farm variation for farmers planting conventional and GM seeds to identify the effect of adoption on the environmental impact of pesticides measured as the quantity of active ingredients of chemicals and the Environmental Impact Quotient index. The findings show that the IR trait reduces the environmental impact of insecticides. However, controversial results have appeared for HT traits, showing a significant increase in the EIQ. Addressing what happened in the last decade, the paper also presents a view of the transformations in GM usage in Brazil, focusing on the considerable success in adopting stacked genes. Future perspectives point to a more diversified menu of technologies, crops, and adopting countries, going beyond platform crops and more prominent agriculture exporters.